Penerapan Sistem Silvikultur pada Hutan Kemasyarakatan di Desa Alu Kecamatan Alu Kabupaten Polewali Mandar - Syaifullah; Ritabulan; Idris, Andi Irmayanti (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2025)
Silvicultural systems play a vital role in the implementation of social forestry programs; however, their application at the community level continues to face various challenges. This study aims to describe silvicultural practices implemented by local communities within the Community Forest (Hutan Kemasyarakatan/HKm) program and to identify the limiting factors influencing their application. The research employed a descriptive qualitative approach, with data collected through observation, interviews, questionnaires, and document analysis. The results indicate that the community of Alu Village has applied a range of silvicultural practices, despite most respondents being unfamiliar with the technical term “silviculture.” Agroforestry is the predominant system adopted, integrating forest tree species such as teak, mahogany, and gmelina with plantation crops including cocoa, coffee, and candlenut, as well as food crops (maize and chili) and fruit trees (durian, rambutan, and nutmeg). Community knowledge related to silvicultural management is largely derived from intergenerational experience, while access to formal extension services remains limited. Constraints affecting the implementation of silvicultural practices can be categorized into technical and non-technical factors. Technical constraints include difficulties in seedling preparation and transportation, limited road access, and unpredictable weather conditions. Non-technical constraints involve limited financial resources, inadequate training opportunities, and insufficient support from relevant institutions.